2021
DOI: 10.1128/iai.00134-21
|View full text |Cite
|
Sign up to set email alerts
|

Aim2 and Nlrp3 Are Dispensable for Vaccine-Induced Immunity against Francisella tularensis Live Vaccine Strain

Abstract: Francisella tularensis (F. tularensis) is a facultative intracellular, Gram-negative bacterium that causes a fatal disease known as tularemia. Due to its extremely high virulence, ease of spread by aerosolization, and the potential to be used as a bioterror agent, F. tularensis is classified by the CDC as a Tier 1 Category A Select Agent. Previous studies have demonstrated the roles of inflammasome sensors; absent in melanoma 2 (AIM2) and NLRP3, in the generation of innate immune responses to F. tularensis inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…AIM2 is a typical inflammasome assembled by the intracellular receptor ALR [ 103 ]. When intracellular pathogen DNA is detected by the HIN200 domain of AIM2, such as the DNA of Francisella tularensis and vaccinia virus [ 75 , 104 ], AIM2 will recruit ASCs to activate caspase-1. The AIM2 receptor is a member of the PYHIN (containing pyrin and HIN domains) family [ 105 , 106 ] and is characterized by its tight binding to oligonucleotides or the oligosaccharide folds between an N-terminal PYD and a C-terminal HIN domain.…”
Section: Inflammasomesmentioning
confidence: 99%
“…AIM2 is a typical inflammasome assembled by the intracellular receptor ALR [ 103 ]. When intracellular pathogen DNA is detected by the HIN200 domain of AIM2, such as the DNA of Francisella tularensis and vaccinia virus [ 75 , 104 ], AIM2 will recruit ASCs to activate caspase-1. The AIM2 receptor is a member of the PYHIN (containing pyrin and HIN domains) family [ 105 , 106 ] and is characterized by its tight binding to oligonucleotides or the oligosaccharide folds between an N-terminal PYD and a C-terminal HIN domain.…”
Section: Inflammasomesmentioning
confidence: 99%
“…Nlrp3 also contributes to the IgA response vital for protection against F. tularensis LVS challenge in immunized mice (Duffy et al, 2016). However, the activation of Aim2 and Nlrp3inflammasomes are repressed in macrophages infected with F. tularensis LVS, and both are dispensable for vaccine-induced immunity against pulmonary tularemia (Atianand et al, 2011;Dotson et al, 2013;Wallet et al, 2016;Alqahtani et al, 2021). It has been reported that Nlrp3 exacerbates the symptoms of pulmonary tularemia primarily by causing excessive infiltration of immature neutrophils in the lungs of mice infected with F. tularensis, indicating a pathogenic role for Nlrp3 (Periasamy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%